Catheter-Directed Thrombolysis of Iliocaval Thrombosis in Patients with COVID-19 (2020)
We present the characteristics and outcomes of the first two cases of catheter-directed thrombolysis performed in patients presenting with COVID-19 related iliocaval thrombosis